Preparation and Characterization of Hyaluronic Acid-Polycaprolactone Copolymer Micelles for the Drug Delivery of Radioactive Iodine-131 Labeled Lipiodol. (3rd January 2017) - Chen, Shih-Cheng; Yang, Ming-Hui; Chung, Tze-Wen; Jhuang, Ting-Syuan; Yang, Jean-Dean; Chen, Ko-Chin; Chen, Wan-Jou; Huang, Ying-Fong; Jong, Shiang-Bin; Tsai, Wan-Chi; Lin, Po-Chiao; Tyan, Yu-Chang
Abstract : Micelles, with the structure of amphiphilic molecules including a hydrophilic head and a hydrophobic tail, are recently developed as nanocarriers for the delivery of drugs with poor solubility. In addition, micelles have shown many advantages, such as enhanced permeation and retention (EPR) effects, prolonged circulation times, and increased endocytosis through surface modification. In this study, we measured the critical micelle concentrations, diameters, stability, and cytotoxicity and the cell uptake of micelles against hepatic cells with two kinds of hydrophilic materials: PEG-PCL and HA-g-PCL. We used 131 I as a radioactive tracer to evaluate the stability, drug delivery, and cell uptake activity of the micelles. The results showed that HA-g-PCL micelles exhibited higher drug encapsulation efficiency and stability in aqueous solutions. In addition, the 131 I-lipiodol loaded HA-g-PCL micelles had better affinity and higher cytotoxicity compared to HepG2 cells.